TREATMENT GOALS ACHIEVED AMONG HYPERTENSIVES AT THE B/A REGIONAL HOSPITAL IN SUNYANI, GHANA. - FORDJOUR, FRANCIS; SODZI, PAUL; BAAH, PHILEMON (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to assess the current success rate of hypertensive patients in achieving blood pressure (BP) treatment goals and to investigate the extent of the consistency in the control of BP following initial achievement. Methods: At the hypertension clinic of the B/A Regional Hospital in Sunyani, Ghana, the current BP of 400 sampled patients, aged 35–100 years was measured. In addition, a retrospective review of nine successive BPs previously recorded in patients’ medical histories was done. Results: Of the 400 patients, women constituted 71.75%. Hypertensive aged ≥60 years represented 64.25% with the rest being ˂60 years. In 58% of patients, there were comorbidities. The adherence to clinic appointment was 54.50%. Of the ten clinic visits, 20.30% of patients ˂60 years were adequately controlled of their BPs while those ≥60 years achieved 33.80% control. In all, 29% of the 400 hypertensives met their treatment goals adequately. Consistency in maintaining a controlled BP at all times was achieved by 23.70% of the 400 patients. Regular visits to clinic was associated with adequate BP control (p˂0.001) while comorbidity was not (p=0.122). Conclusion: Treatment goals’ achievement by hypertensives at the Regional Hospital in Sunyani, Ghana, was relatively low. Consistency in maintaining a controlled BP while on medication is poor. The lack of consistency in keeping a controlled BP may contribute to the increased cardiovascular deaths among hypertensives. Intensive mass education and treatment optimization are required to deal with treatment failures among patients.